Diagnosis of Capnocytophaga canimorsus Sepsis by Whole-Genome Next-Generation Sequencing. (12th July 2016) - Abril, Maria K.; Barnett, Adam S.; Wegermann, Kara; Fountain, Eric; Strand, Andrew; Heyman, Benjamin M.; Blough, Britton A.; Swaminathan, Aparna C.; Sharma-Kuinkel, Batu; Ruffin, Felicia; Alexander, Barbara D.; McCall, Chad M.; et al.
Abstract: We report the case of a 60-year-old man with septic shock due to Capnocytophaga canimorsus that was diagnosed in 24 hours by a novel whole-genome next-generation sequencing assay. This technology shows great promise in identifying fastidious pathogens, and, if validated, it has profound implications for infectious disease diagnosis.